Application of the enhanced sono-photo‑Fenton-like process in the presence of persulfate for the simultaneous removal of chromium and phenol from the aqueous solution. (April 2020) - Yazdanbakhsh, Ahmadreza; Aliyari, Asma; Sheikhmohammadi, Amir; Aghayani, Ehsan
Abstract: This study was conducted to investigate the enhanced sono-photo‑Fenton-like process (SPFP) in the presence of persulfate, as a method of Advanced Oxidation Processes (AOPs) to generate oxidative radicals (O2 −, OH, SO4 − ) for the simultaneous removal of chromium and phenol from aqueous solutions. The removal performance of chromium and phenol by UV alone, UV/H2 O2 (UH), UV/H2 O2 /Fe 0 (UHF), UV/H2 O2 /Fe 0 /S2 O8 (UHFS) and UV/H2 O2 /Fe 0 /S2 O8 /US (UHFSU) were estimated (12.5, 6.5 %), (35.1, 31 %), (52.5, 66.1 %), (74.9, 79.1 %) and (100, 100 %), respectively under selected conditions (phenol/chromium molar ratio, 2.0; pH, 3.0; H2 O2 /Fe 0 molar ratio, 2.0; S2 O8, 0.75 mM L −1 and reaction time, 4 min). Also, according to obtained results, robs value for UHFSU process in the removal of (chromium and phenol) was about (14.62, 30.84), (10, 4), (7.64, 2.47) and (3.2, 1.3) times than that of the UV alone, UH, UHF and UHFS, respectively. The study of the energy consumption for the various processes indicated the UHFSU process compared with other processes, has very low energy consumption (kWh m -3 ), which proves the process justification economically. The addition of the various scavengers (ammonium oxalate, 2-propanol and tert-butanol) was diminished the removal performance; it clearly proved oxidative radicals (O2 −, OH, SO4 − ) plays a noticeable role in the removal of chromium and phenol.